Experimental study of palm oil mill effluent and oil palm frond waste mixture as an alternative biomass fuel - Hassan, S. (2013)
Palm oil mill effluent (POME) sludge generated from palm oil mill industry and oil palm frond (OPF) from oil palm plantation are considered biomass wastes that can be fully utilized as a renewable energy sources. In this study, an attempt has been made to convert these residues into solid biomass fuel. The study was conducted by developing experimental testing on the POME and OPF mixture. The performance of each sample with different weight percentage was investigated using standard tests. The biomass mixture was converted into compressed form of briquette through a simple process. The properties of the briquettes were observed and compared at different weight percentage following standard testing methods included ultimate and proximate analyses, burning characteristics, dimensional stability and crack analysis. Experimental results showed that POME sludge and OPF mixture is feasible as an alternative biomass fuel, with briquette of 90:10 POME sludge to OPF ratio has a good combination of properties as an overall. Â© School of Engineering, Taylor's University.